"Los my poes af" – the fine line between being radical enough and being too radical. Issue 2 (3rd April 2019) - Hartmann, Laura
Abstract: The majority of civil society organisations in Cape Town are run by black and coloured women who are fighting against increasing crime rates, especially relating to the abuse of women and children. Besides the fight against violence, women also face the daily struggle of saving their organisations and ensuring enough financial support to continue the work they are doing. Lucinda Evans, woman leader and human rights activist from Lavender Hill, elaborates on how women's organisations from the Cape Flats in Cape Town are walking the fine line between being radical enough and being too radical, especially when it comes to open protest in the streets. Organisations that are aligned with government, political parties or international charity organisations not only receive financial support, but are obliged to make certain compromises. Part of these compromises is the agreement to maintain a professional public image, which would inhibit the fight against violence on the Cape Flats, as Evans explains. This focus piece elaborates on the external influences which control women's activism in South Africa and on conclusions that can be drawn from these restrictions. It demonstrates exemplarily how women activists are torn between publicly demanding their rights and jeopardising the organisations they are running.